2018
DOI: 10.1021/acs.est.8b03206
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Organic Matter on Iron(II)-Catalyzed Mineral Transformations in Ferrihydrite–Organic Matter Coprecipitates

Abstract: Poorly crystalline Fe(III) (oxyhydr)oxides like ferrihydrite are abundant in soils and sediments and are often associated with organic matter (OM) in the form of mineralorganic aggregates. Under anoxic conditions, interactions between aqueous Fe(II) and ferrihydrite lead to the formation of crystalline secondary minerals, like lepidocrocite, goethite, or magnetite. However, the extent to which Fe(II)-catalyzed mineral transformations are influenced by ferrihydrite-associated OM is not well understood. We there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
195
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 175 publications
(219 citation statements)
references
References 75 publications
24
195
0
Order By: Relevance
“…This is in agreement with reports of X-ray amorphous, nanometersized clusters of secondary mineral phases forming during reactions between dissolved Fe(II) and ferrihydrite in the presence of OM at circumneutral pH. [37][38][39]50,63 The importance of non-sulfur-associated Fe(II) during sulfidization reactions was also noted by Peiffer et al, 15 who demonstrated that conditions which favored its formation in excess hindered FeS precipitation. Similarly, Kumar et al 16 suggested that a minimum S(−II)/Fe molar ratio of 0.5 was required for mackinawite accumulation.…”
Section: Trends In Aqueous S and Fesupporting
confidence: 90%
See 4 more Smart Citations
“…This is in agreement with reports of X-ray amorphous, nanometersized clusters of secondary mineral phases forming during reactions between dissolved Fe(II) and ferrihydrite in the presence of OM at circumneutral pH. [37][38][39]50,63 The importance of non-sulfur-associated Fe(II) during sulfidization reactions was also noted by Peiffer et al, 15 who demonstrated that conditions which favored its formation in excess hindered FeS precipitation. Similarly, Kumar et al 16 suggested that a minimum S(−II)/Fe molar ratio of 0.5 was required for mackinawite accumulation.…”
Section: Trends In Aqueous S and Fesupporting
confidence: 90%
“…Moreover, the fraction of crystalline minerals (lepidocrocite + magnetite + goethite + pyrite) at 12 months was higher in the absence of OM (x _ = 65% vs. x _ = 16%). Collectively, these findings support Henneberry et al 40 and suggest that, similar to Fe(II)catalyzed reactions, [37][38][39]50,63 OM inhibits ferrihydrite mineral transformations and the formation of secondary crystalline phases in the presence of reduced S species.…”
Section: Impact Of Om On Ageing Of Sulfidized Ferrihydritesupporting
confidence: 84%
See 3 more Smart Citations